2017
DOI: 10.3389/fpls.2017.00744
|View full text |Cite
|
Sign up to set email alerts
|

Identification of High-Temperature Tolerant Lentil (Lens culinaris Medik.) Genotypes through Leaf and Pollen Traits

Abstract: Rising temperatures are proving detrimental for various agricultural crops. Cool-season legumes such as lentil (Lens culunaris Medik.) are sensitive to even small increases in temperature during the reproductive stage, hence the need to explore the available germplasm for heat tolerance as well as its underlying mechanisms. In the present study, a set of 38 core lentil accessions were screened for heat stress tolerance by sowing 2 months later (first week of January; max/min temperature >32/20°C during the rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
121
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 119 publications
(147 citation statements)
references
References 73 publications
20
121
0
Order By: Relevance
“…Our studies showed that heat stress at the time of seed filling drastically reduced the components of yield and quality of seeds in both heat‐tolerant (HT) and heat‐sensitive (HS) lentil genotypes. We previously reported the damaging effects of high temperature on traits related to pollen function in lentil, which were associated with pod set and seed yield . In the present study, we investigated the adverse effects of heat stress on seed quality in lentil genotypes using proximate analysis and other seed component analyses.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our studies showed that heat stress at the time of seed filling drastically reduced the components of yield and quality of seeds in both heat‐tolerant (HT) and heat‐sensitive (HS) lentil genotypes. We previously reported the damaging effects of high temperature on traits related to pollen function in lentil, which were associated with pod set and seed yield . In the present study, we investigated the adverse effects of heat stress on seed quality in lentil genotypes using proximate analysis and other seed component analyses.…”
Section: Discussionmentioning
confidence: 95%
“…Lentil ( Lens culinaris Medikus) is a vital cool‐season crop that is highly sensitive to rising temperatures . Lentil requires low temperatures at the time of vegetative growth but warm temperatures to mature; optimum growth occurs from 18–30 °C .…”
Section: Introductionmentioning
confidence: 99%
“…4. The observed decrease in pollen germination under heat stress at or during anthesis can be associated with damages to pollen physical structure, pollen wall composition, or lower energy (sugar) status (Jagadish et al, 2010;Jiang et al, 2015;Djanaguiraman et al, 2017a;Sita et al, 2017). 1) and grain filling (HS Grain-filling for 30 d in Exp.…”
Section: Discussionmentioning
confidence: 99%
“…High temperature is frequently associated with reduced availability of water; hence, crops grown in tropical and subtropical environments need to be evaluated for their responses to the combination of heat and drought stress (Barnabás et al, ). The individual effects of heat and drought stress have been investigated in many crops (Shanker et al, ) including lentil (Sita et al, ); however, studies on their combined effects are less common, despite being strongly associated and having severe impact on growth and productivity of several crops (Cvikrová, Gemperlová, Martincová, & Vanková, ; Lipiec, Doussan, Nosalewicz, & Kondracka, ; Lobell et al, ; Nankishore & Farrell, ; Prasad, Pisipati, Momcilovic, & Ristic, ; Rollins et al, ; Shinohara & Leskovar, ). The occurrence of drought, accompanied by heat stress, is likely to increase in the near future (IPCC, ), which highlights the need to investigate crop responses to combined heat and drought stresses (Zandalinas, Mittler, Balfagon, Arbona, & Gomez‐Cadenaz, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cool‐season food legumes are adapted to low and mild temperature environment and hence show high sensitivity to heat stress, as observed in chickpea (Kaushal et al, ) and lentil (Sita et al, ). Our earlier studies have indicated lentil ( L. culinaris Medikus) to be more sensitive than chickpea to high temperature, both at vegetative as well as reproductive stages (Bhandari et al, ; Sita et al, ). The optimum temperatures for lentil growth range from 18 to 30 °C (Sinsawat et al ; Roy, Tarafdar, Das, & Kundagrami, ), with warm temperatures needed for maturity.…”
Section: Introductionmentioning
confidence: 99%